The Fe/S cluster assembly protein Isd11 is essential for tRNA thiolation in Trypanosoma brucei - Paris, Zdenek; Changmai, Piya; Rubio, Mary Anne T; Zíková, Alena; Stuart, Kenneth D; Alfonzo, Juan D; Lukes, Julius (The Journal of biological chemistry, 2010)
Fe/S clusters are part of the active site of many enzymes and are essential for cell viability. In eukaryotes the cysteine desulfurase Nfs (IscS) donates the sulfur during Fe/S cluster assembly and was thought sufficient for this reaction. Moreover, Nfs is indispensable for tRNA thiolation, a modification generally required for tRNA function and protein synthesis. Recently, Isd11 was discovered as an integral part of the Nfs activity at an early step of Fe/S cluster assembly. Here we show, using a combination of genetic, molecular, and biochemical approaches, that Isd11, in line with its strong association with Nfs, is localized in the mitochondrion of T. brucei. In addition to its involvement in Fe/S assembly, Isd11 also partakes in both cytoplasmic and mitochondrial tRNA thiolation, whereas Mtu1, another protein proposed to collaborate with Nfs in tRNA thiolation, is required for this process solely within the mitochondrion. Taken together these data place Isd11 at the center of these sulfur transactions and raises the possibility of a connection between Fe/S metabolism and protein synthesis, helping integrate two seemingly unrelated pathways.
Keywords: akonitáthydratasa; Fumarate Hydratase; membránový potenciál mitochondrií; RNA interference; Cytosol; RNA protozoální; RNA, Transfer; Phenotype; Aconitate Hydratase; RNA, Protozoan; mitochondrie; mitochondriální proteiny; RNA transferová; Protein Stability; stabilita proteinů; Trypanosoma brucei brucei; RNA Interference; Mitochondrial Proteins; Sulfhydryl Compounds; Protozoan Proteins; sulfhydrylové sloučeniny; protozoální proteiny; cytosol; fumarasa; Membrane Potential, Mitochondrial; fenotyp; Iron-Sulfur Proteins; Mitochondria; proteiny obsahující železo a síru